2015
DOI: 10.1016/j.fuel.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nascent char structure during the gasification of low-rank coals in CO2

Abstract: 25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…These relationships explain that HVBC coal is more reactive than its respective chars, because of its middle-ranking, lessordered structure which cause their lower reactivity index under devolatilization. Additionally, the results reveal that HVBC chars obtained under N 2 atmosphere are less reactive than those from CO 2 , which is consistent with the results presented in Figure 13 (dashed lines) and obtained by Zhang et al (2015), for a similar rank coal. Those researchers attributed this difference to a high concentration of defects in the crystal structure caused by the reaction atmosphere, differences in heating rate, and to the greater energy density of CO 2 compared to N 2 , which leads to a lower value of the I G /I ALL relationship in the structure of the char obtained under CO 2 .…”
Section: Correlation Between Structural Changes and Char Reactivitysupporting
confidence: 90%
“…These relationships explain that HVBC coal is more reactive than its respective chars, because of its middle-ranking, lessordered structure which cause their lower reactivity index under devolatilization. Additionally, the results reveal that HVBC chars obtained under N 2 atmosphere are less reactive than those from CO 2 , which is consistent with the results presented in Figure 13 (dashed lines) and obtained by Zhang et al (2015), for a similar rank coal. Those researchers attributed this difference to a high concentration of defects in the crystal structure caused by the reaction atmosphere, differences in heating rate, and to the greater energy density of CO 2 compared to N 2 , which leads to a lower value of the I G /I ALL relationship in the structure of the char obtained under CO 2 .…”
Section: Correlation Between Structural Changes and Char Reactivitysupporting
confidence: 90%
“…The same conclusion was reached in the study of Zhang et al. [100,101] Lievens et al [112] reported the structure of Inner Mongolia low-rank coal, concluding that its aromatic ring structures consisting of 59% amorphous structures (G L , G, G R , V L , and V R bands), 22% highly ordered structures with no less than six rings (D band), 16% aromatic structures characterized by aliphatic and/or ether substitutions (S L , S bands), and 3% substituted benzene rings (S R , R bands).…”
Section: Study Of Coal's Functional Groupssupporting
confidence: 83%
“…In recent years, some researchers [100][101][102][103][104][105][106][107][108][109][110][111][112] studied the structure of coal by using Raman spectroscopy and referring to the curve-fitting method by Li et al [53,86,87] Zhang et al [100,101] considered the structural changes of semicoke during the rapid pyrolysis of wood and low-rank coal at 600-1,200 C and got similar result of Li et al Wang et al [102] reported that the A…”
Section: Study Of Coal's Functional Groupsmentioning
confidence: 94%
“…Only four significant peaks were observed in ashes spectra. On the other hand, -CH 3 /-CH 2 Other authors [40] studied gasification of two low-range carbons, finding out similar spectra in the wavelength range of 1800-600 cm −1 . They suggested that during gasification process different kinds of functional groups with oxygen were formed (C = O bonds) which were mainly tied to aromatic rings such as phenolic groups, enhancing dipole moment of the vibration of aromatic rings and vibration intensity by the stretching of C = C bond in those aromatic rings.…”
Section: Ftir Analysismentioning
confidence: 85%